Time dependence of interactions between a surfactant-coated substrate and a uniformly charged surface. - Silbert, G; Kampf, N; Perkin, S; Klein, J (2012)
Using the surface force balance (SFB), we recorded the changes with time of the adhesion, normal, and shear interactions between a monolayer of cetyltrimethylammonium bromide (CTAB) on mica and a bare mica surface across surfactant-free water. In this asymmetric case, the bare mica acts a stable probe of the interactions between the two surfaces as the CTAB-coated one undergoes changes with time. As previously demonstrated, when a CTAB monolayer on mica is immersed in water, it reorganized to form bilayer patches, exposing the bare mica surface, followed by a gradual release of free surfactants to the bulk. We probe how this degradation with time affects both the normal force vs distance interaction profiles, and adhesion between the CTAB-coated surface and a bare mica surface. We demonstrate that the CTAB layer leads to a reduction in the sliding friction relative to that between bare mica surfaces, which is reversed only at advanced degradation levels, whereupon an abrupt increase in the friction occurs. This change is ascribed to adhesion between exposed bare mica surfaces, which sets on when the density of CTAB patches is low. The reproducibility of the normal force profiles and of adhesion forces on sequential approaches at the same contact spot indicates that there is no substantial transfer of materials between the surfaces while they are in adhesive contact.